Estrategias metodológicas para potenciar la educación ambiental en la formación integral de los niños y niñas del quinto grado del subnivel básica media de la escuela de educación general básica Graciela Atarihuana de Cueva de la ciudad y provincia de Loja, período lectivo 2013 – 2014 - Guamán Sigcho, Alexandra Graciela (2015)
This ts investigated the methodological strategies to promote Environmental Education within the curriculum of students in fifth grade of elementary (medium basic sublevel) education in “Graciela AtarihuanaCueva” School in Loja City, Province of Loja, in the school year 2013 – 2014. The methodology used was a survey of the students, and an interview with the teacher then analytic-synthetic, inductive-deductive methods were used. The population investigated was made up of the fifth-grade students and their respective teacher. The analysis and interpretation of results revealed a lack of knowledge in the use of methods to educate students to care for the environment. The educational strategies and teaching materials used by the educator were not sufficiently attractive for the students to arouse an interest in Environmental Education which was the underlying problem within the institution. To improve this situation various ecological workshops were held within this investigation providing an improved learning experience including role play, as a learning strategy, and as a result the teacher learned this technique and the students acquired an awareness of environmental responsibility.